UJI SIFAT GLISERIN DENGAN STANDARISASI - Masdania Zurairah (Bajang Institute, 2024)
The glycerin produced at PT However, when companies produce glycerin, there are variations between the actual technical characteristics (namely color, odor, acid number and water content) and the standard glycerin produced. Comparison of technical characteristics of actual and standard glycerin. In this case, color results were obtained that did not meet the glycerin standard of 99.6%, where the glycerin standard was around 96.7% - 97.3, while those that did not meet the physical properties of odor were 0.024% and 0.074% and the glycerin standard regarding odor was between 0.03-0.07%. The standard glycerol level reaches pH 4.8-5.2 and is obtained which does not meet pH 2.8, 7.4, 7.5, 7.8. The standard level of glycerin in water is 0.4% - 05% which does not meet the water content of 0.22% and 0.69%